2008
DOI: 10.1080/00365510701466416
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of osteogenesis of human embryonic stem cells within 2D and 3D culture systems

Abstract: The objective of this study was to compare the osteogenic potential of human embryonic stem cells (hESCs) within two- and three-dimensional (2D and 3D) culture systems. hESCs of the H1 line (Wicell Inc., Madison, Wisc., USA) were induced to form embryoid bodies (EBs) through 5 days of suspension culture within non-adherent culture dishes. Following enzymatic dissociation, the EB-derived single cells were seeded on either novel 3D porous PLGA scaffolds or 2D culture dishes with the same total cell number. Osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 28 publications
5
52
1
Order By: Relevance
“…Osteogenic differentiation has been shown in samples following EB dissociation before osteogenic culture. 63,64 Results showed that settled EB cultures exhibited greater osteogenic differentiation than dissociated EB cultures, demonstrating that continued 3D cell-cell and cellmatrix interaction benefited osteogenic differentiation, which has been previously reported 63,65 (Fig. 4E, G).…”
Section: Discussionsupporting
confidence: 79%
“…Osteogenic differentiation has been shown in samples following EB dissociation before osteogenic culture. 63,64 Results showed that settled EB cultures exhibited greater osteogenic differentiation than dissociated EB cultures, demonstrating that continued 3D cell-cell and cellmatrix interaction benefited osteogenic differentiation, which has been previously reported 63,65 (Fig. 4E, G).…”
Section: Discussionsupporting
confidence: 79%
“…These observations are supported by several studies that have shown cellular function significantly differs in 2D microenvironments relative to their 3D counterparts. [24][25][26][27] Therefore, developing 3D microarray platforms is important for studying stem cell differentiation in a high-throughput manner. 10,23,28 In one such study Dordick and colleagues 28 developed a 3D cellular microarray platform that could be used to track and quantify stem cell behavior.…”
Section: Commentarymentioning
confidence: 99%
“…One is that 3D culture systems using scaffolds can provide cell-to-cell and/or cell-to-matrix interactions. These interactions promote differentiation of ES cells and construction of tissue-like structures (Carlberg et al, 2009, Elisseeff et al, 2006, Gao et al, 2010, Tian et al, 2008, Yim et al, 2006. Another benefit of the 3D culture system is that it can be manipulated to retrieve the cells or tissues derived from EBs without injuring or destroying them.…”
Section: Advantage Of the 3d Culture Systems And Imitation Of In Vivomentioning
confidence: 99%